2014
DOI: 10.11648/j.sjac.20140204.12
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Some Volatile Compounds in Fruit Spirits Produced from Grapes (Vitis Vinifera L.) and Plums (Prunus domestica L.) Cultivars

Abstract: Abstract:Fruit spirits contain a large array of volatile compounds among which the important role from toxicological aspect besides ethanol has methanol, aliphatic esters and fusel alcohols. This study evaluates the content of ethanol, ethyl acetate, methanol, isopropyl alcohol (2-propanol), n-propyl alcohol (propan-l-ol), isobutyl alcohol (2-methylpropan-1-ol), n-butyl alcohol (1-butanol), isoamyl alcohol (3-methyl-1-butanol) and n-amyl alcohol (pentan-1-ol) in different grapes and plum brandies industrially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Mendonca et al ( 2011 ) reported 0.05–0.189 % methanol in cachaca produced from banana pulp, while Dato et al ( 2005 ) reported 0.00–0.50 % methanol in cachaica produced from sugarcane in Brazil. Plum wine (Joshi et al 2009 ; Jung et al 2010 ), plum brandy (Kostik et al 2014 ), agave (Leon-Rodriguez et al 2008 ) contain methanol. The substrate for ethanol production is the first probable source of methanol in the beverage.…”
Section: Methanol Contamination In Fermented Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendonca et al ( 2011 ) reported 0.05–0.189 % methanol in cachaca produced from banana pulp, while Dato et al ( 2005 ) reported 0.00–0.50 % methanol in cachaica produced from sugarcane in Brazil. Plum wine (Joshi et al 2009 ; Jung et al 2010 ), plum brandy (Kostik et al 2014 ), agave (Leon-Rodriguez et al 2008 ) contain methanol. The substrate for ethanol production is the first probable source of methanol in the beverage.…”
Section: Methanol Contamination In Fermented Beveragesmentioning
confidence: 99%
“…Traditional fermentation is carried out by mixed cultures consisting of yeast, other fungi and bacteria. Though, most of the traditionally fermented food and beverages are dominated by the yeast Saccharomyces cerevisiae, and to a lesser extent Lactobacillus (Jespersen 2003 ; Ogbulie et al 2007 ; Karamoko et al 2012 ; Rokosu and Nwisienyi 1980 ), the presence of other microbes can lead to the production of diverse products including methanol (Dato et al 2005 ; Shale et al 2013 ; Kostik et al 2014 ). Several compounds could be produced during mixed fermentation with several organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Esters are very important compounds due to their particular contribution to flavour and aroma, since they have the lowest organoleptic threshold [41]. The quantity of this compound presented in the final product can vary widely, since it is synthesized from acetic acid and ethanol [42].…”
Section: Estersmentioning
confidence: 99%
“…Esters are however very important compounds due to their particular contribution to flavour and aroma, since they have the lowest organoleptic threshold [32]. The quantity of this compound presented in the final product can vary widely, since it is synthesized from acetic acid and ethanol [33].…”
Section: Estersmentioning
confidence: 99%